Effect of soil texture on nitrogen mineralization from organic fertilizers in four common southeastern soils. Issue 2 (29th March 2020) - Cassity‐Duffey, Kate; Cabrera, Miguel; Franklin, Dory; Gaskin, Julia; Kissel, David
Abstract: Previous studies have indicated that soil properties and texture could lead to differences in N mineralization from applied organic materials. We conducted a 100‐day (d) incubation study to measure net N mineralized from feather meal (14–0.1–0.1) and pellet mix (10–1–6) at 150 mg N kg soil −1 (approximately 72 kg N ha −1 ) incorporated into four common southeastern soils: Cecil 1, Cecil 2, Greenville, and Tifton. A second 23‐d study was conducted to determine pH dynamics and the potential for ammonia volatilization from the same soils and materials. There were no differences in net N mineralized from pellet mix among soils, but net N mineralized from feather meal was lower in Greenville soil, which had the greatest clay content. Analysis of the first‐order dynamics of N mineralization indicated that even in soils that differ in clay content it may be possible to describe N mineralization from feather meal and pellet mix with a single model. Our results also suggest that the effect of pH on the N mineralization dynamics of these fertilizers may be more important than the effect of clay content. No ammonia loss was observed regardless of soil texture, soil pH buffering capacity, or initial soil pH.